Representasi Realitas Dalam Pikiran Anak: Studi Kualitatif Tentang Dampak Konten Digital Anomali Terhadap Persepsi Anak Usia Dini Di KB Al-Hilmiyah - Mufarrohah Mufarrohah; Abd Rosyid; Desi Ismawati (ABATATSA: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The development of digital technology has made it increasingly easy for young children to be exposed to various social media content, including anomalous digital content that is absurd and inconsistent with the logic of reality. At the preoperational stage of development, this condition has the potential to cause confusion in children distinguishing between fantasy and reality. This study aims to analyze the impact of anomalous digital content on the perception of reality in young children. This study used qualitative methods with observation and interview techniques. The study was conducted at Al-Hilmiyah Kindergarten, Pasanggar Village, Pamekasan Regency, involving teachers, the principal, and parents. Data were analyzed descriptively. The results indicate that exposure to anomalous digital content affects how children perceive reality, characterized by imitation of inappropriate behavior and language, conceptual confusion between fantasy and reality, and decreased attention span. However, through guidance and preventative measures undertaken by the school, children began to exhibit more positive behavior. These findings emphasize the important role of parents and educators in guiding the use of digital media in young children.